Crossbreeding parameters for growth traits in a complete three breeds diallel cross design of rabbits in Egypt - Abdel-Hamid, Tamer Mohamed (Journal of Advanced Veterinary and Animal Research, 2015)
The present study was conducted to estimate crossbreeding parameters for growth traits of growing rabbits in a complete 3 × 3 diallel crossing experiment involving three breeds namely New Zealand White (NN), Californian (CC) and Rex (RR). Highly significant differences (p?0.001) were observed among different genotypes for almost traits studied with the exception of relative growth rates (RGR) at 4-12 weeks of age. Direct genetic effects of NN were found as positive for most of studied traits. Positive total maternal genetic effect was estimated for kits of NN dose for weight at weaning (57 g) and 12 weeks of age (92 g). Strong individual heterosis was estimated for NN × CC crossbreds for all body weight (BW) and most of body weight gains (BWG). In conclusion, direct additive genetic effects were infavor NN for growth traits and maternal genetic effects were infavor NN for weaning and final weights and higher individual heterosis has been estimated for NN × CC crossbred rabbits for growth traits. http://dx.doi.org/10.5455/javar.2015.b60